Trichomonas vaginalis Virus Among Women With Trichomoniasis and Associations With Demographics, Clinical Outcomes, and Metronidazole Resistance. (15th February 2019) - Graves, Keonte J; Ghosh, Arindam P; Schmidt, Norine; Augostini, Peter; Secor, W Evan; Schwebke, Jane R; Martin, David H; Kissinger, Patricia J; Muzny, Christina A
Abstract: Background: Trichomonas vaginalis virus (TVV) is a non-segmented, 4.5–5.5 kilo-base pair (kbp), double-stranded RNA virus infecting T. vaginalis . The objectives of this study were to examine the TVV prevalence in US Trichomonas vaginalis isolates and TVV's associations with patient demographics, clinical outcomes, and metronidazole resistance. Methods: Archived T. vaginalis isolates from the enrollment visits of 355 women participating in a T. vaginalis treatment trial in Birmingham, Alabama, were thawed and grown in culture. Their total RNA was extracted using a Trizol reagent. Contaminating, single-stranded RNA was precipitated using 4.0 M Lithium Chloride and centrifugation. The samples were analyzed by gel electrophoresis to visualize a 4.5 kbp band representative of TVV. In vitro testing for metronidazole resistance was also performed on 25/47 isolates obtained from the women's test of cure visits. Results: TVV was detected in 142/355 (40%) isolates at the enrollment visit. Women with TVV-positive (TVV+) isolates were significantly older ( P = .01), more likely to smoke ( P = .04), and less likely to report a history of gonorrhea ( P = .04). There was no association between the presence of clinical symptoms or repeat T. vaginalis infections with TVV+ isolates ( P = .14 and P = .44, respectively). Of 25 test of cure isolates tested for metronidazole resistance, 0/10 TVV+ isolates demonstrated resistance, while 2/15 TVV-negative isolates demonstrated mild to moderate resistance ( P = .23). Conclusions: Of 355 T. vaginalis isolates tested for TVV, T. vaginalis isolates tested for TVV, the prevalence was 40%. However, there was no association of TVV+ isolates with clinical symptoms, repeat infections, or metronidazole resistance. These results suggest that TVV may be commensal to T. vaginalis . Abstract : Among women with trichomoniasis, Trichomonas vaginalis virus (TVV) infected 142/355 (40%) of T. vaginalis isolates and was independently associated with older age and smoking. Women reporting a history of gonorrhea were less likely to be infected. Metronidazole drug resistance was not associated with TVV.